2020
DOI: 10.1177/0261429420917854
|View full text |Cite
|
Sign up to set email alerts
|

Teaching higher order thinking skills to gifted students: A meta-analysis

Abstract: The current study examined the effects of higher order thinking skills (HOTS) interventions with gifted students in Taiwan. A total of 25 studies published between 1997 and 2017 were included. Twenty-nine effect sizes were extracted for the 25 studies. The small number of existing studies indicates a lack of scholarly attention to HOTS in gifted education in Taiwan in the past two decades. On the other hand, the effect sizes, ranged from 0.26 to 2.01, with a mean of 0.78 and standard deviation of 0.39, showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…These findings also indicate the benefits of having an affective curriculum that exposes students to critical sociocultural issues and encourages them to gather to debate such issues (Hébert, 2012; Jen et al, 2016; Peterson, 2000). This is helpful not only for creating an open and accepting classroom milieu (Hébert et al, 2014) but also for attuning to the intellectual potential (e.g., addressing complexity) of these cognitively highly capable students (Dixon et al, 2004; Lo & Feng, 2020). Kanevsky et al (2021) also indicated that gifted students prefer learning with others when the learning tasks address complex issues where diverse perspectives are beneficial to the project assigned.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also indicate the benefits of having an affective curriculum that exposes students to critical sociocultural issues and encourages them to gather to debate such issues (Hébert, 2012; Jen et al, 2016; Peterson, 2000). This is helpful not only for creating an open and accepting classroom milieu (Hébert et al, 2014) but also for attuning to the intellectual potential (e.g., addressing complexity) of these cognitively highly capable students (Dixon et al, 2004; Lo & Feng, 2020). Kanevsky et al (2021) also indicated that gifted students prefer learning with others when the learning tasks address complex issues where diverse perspectives are beneficial to the project assigned.…”
Section: Discussionmentioning
confidence: 99%
“…HOTS stands for higher order thinking skills. Higher order thinking skills contain several sequences of thinking criteria, including being able to understand, apply, analyze, evaluate and create (Lo & Feng, 2020). HOTS has three points.…”
Section: Introductionmentioning
confidence: 99%
“…Application of students' HOTS and critical thinking can be implemented through the application of student assessments. According to Lo & Feng (2020), assessment is the process of getting information about student learning abilities referring to the evaluation of overall student performance in generating assumptions about learning which includes student quality and achievement. In simple, assessment is a method in assessing the materials that are correspond with students' needs and their learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…With a little bit of difference, most researches all mention three most important parts in higher-order thinking skills, namely, critical thinking skills, problem-solving strategy, and creativity. Higher-order thinking skills are highly valued, just as it was mentioned by the World Economic Forum in 2016 that critical thinking and complex problem-solving will sure be the most demanded job qualifications [10]. Wu Yan (2018), the Director of Higher Education Department of Ministry of Education, put forward the "golden lesson" standard in the National University Teaching Forum, in which higher-order is interpreted as a fusion of knowledge, ability, and quality with the aim of cultivating students' advanced thinking ability and comprehensive ability to solve complicated problems [11].…”
Section: Introductionmentioning
confidence: 99%